PENGARUH PENGGUNAAN APLIKASI KIPIN SCHOOL TERHADAP HASIL BELAJAR JARAK JAUH MATA PELAJARAN PAI DI KELAS V-A SDN KEDUNG WARINGIN 02 BOGOR PADA MASA PANDEMI COVID-19 - Rahmawati, Deby; Nurlaeli, Acep; Suryana, Suyan (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
This research examines the influence and magnitude of the Kipin School application on distance learning outcomes for PAI subjects in class V-A at SDN Kedung Waringin 02 Bogor during the Covid-19 pandemic. This research approach is quantitative with a Pre-Experimental research design which is designed using an experimental method with a single treatment design. Meanwhile, data analysis in this research uses a simple linear regression test, namely Y = 32.206 + 0.666. To test the relationship between the Kipin School application (X) and distance learning outcomes (Y), a product moment correlation test was carried out which aims to get the results of a 2-way hypothesis test by comparing Rcount > Rtable = 0.757 > 0.361. These results state that there is an influence between variable From the results of the product moment correlation test, the correlation coefficient value is 0.757 or is in the good significance category of 0.000 < 0.05, which means the data has a significant effect. The magnitude of the influence in this research can be seen from the Rsquare in the "model summary" table with a value of 0.574 or 57.4% and the remaining 0.426 or 42.6% are factors not examined in this research. Therefore, it can be concluded that the Kipin School application has an influence on distance learning outcomes. The implications of this research include: 1) increasing the effectiveness of distance learning, 2) support for new learning, 3) increasing teacher creativity training.